(untitled) (The Review of Diabetic Studies, 2025)
Telemedicine has emerged as a transformative innovation in modern healthcare, redefining how patients and healthcare providers interact, communicate, and deliver medical services. As technological advancements continue to reshape global industries, healthcare has been significantly influenced by the integration of digital tools and remote communication systems. Telemedicine represents a pivotal solution that bridges geographical gaps, enhances accessibility, and improves the efficiency of healthcare management. It allows patients to receive medical consultations, follow-ups, and monitoring without the constraints of physical visits, making healthcare more patient-centered and responsive to individual needs (Ezeamii et al., 2024).